Cigarette demand in Malaysia - Mohamed Nor, Norashidah (Universiti Putra Malaysia Press, 2012)
Tobacco use is the leading cause of several preventable disease and premature death in the world today. It is estimated more than 14,000 people die every day and if current trend continue, more than eight million people will die by 2030. 80% of these premature deaths are happening in developing countries (WHO, 2008). Among the tobacco products, cigarette is the most commonly consumed. In this book,demand for cigarette is empirically examined using demand models. The estimated price elasticity of demand for cigarette is inelastic and price is a significant determinant of demand for cigarette in the long run.The findings suggested that cigarette is an additive good and the addiction of cigarette among Malaysian smokers is due to their myopic behavior. According to myopic addiction hypothesis, they only considered their past consumption of cigarette but ignored future consumption when making current decision to smoke. Beside price, income per capita and number of youth population have a positive relationship with the consumption for cigarette and significant determinants.